THE ORIGIN OF LETTUCE AND METHODS OF GROWING IT ON A GLOBAL SCALE (BASED ON HYDROPONICS). - Kuchkorova Gulasal (TADQIQOTLAR, 2025)
Abstract Lettuce (Lactuca sativa L.) is a globally recognized leafy vegetable known for its nutritional value and versatility. The cultivation of lettuce in hydroponic systems, specifically  using  the  Nutrient  Film  Technique  (NFT)  and  Deep  Flow  Technique (DFT), has gained popularity for its efficiency and environmental sustainability. This study  explores  the  effects  of  biofertilizers,  including  Plant  Growth-Promoting Rhizobacteria (PGPR), Arbuscular Mycorrhizal Fungi (AMF), and microalgae, on the growth performance of lettuce in hydroponic systems. Lettuce plants were grown under controlled environmental conditions, with consistent nutrient solution management, including pH and electrical conductivity adjustments. Biofertilizers were applied at different concentrations (50% MF + B, 50% MF + AMF, 50% MF + microalgae) to assess their influence on growth parameters such as leaf area, leaf number, plant height, and  biomass.  The  results  revealed  that  biofertilizers  significantly  improved  lettuce growth, with PGPR treatment yielding the greatest increase in leaf area and biomass. These biofertilizers contributed to enhanced nutrient availability and improved root health, promoting better growth compared to control groups. The findings highlight the potential  of  biofertilizers  to  optimize  hydroponic  lettuce  production  by  improving resource  use  efficiency  and  fostering  sustainable  agricultural  practices.  This  study offers  valuable  insights  into  hydroponic  lettuce  cultivation  and  the  integration  of biofertilizers as a promising solution for improving plant growth and yield in controlled environments.